PENYALAHGUNAAN NARKOBA BAGI KALANGAN REMAJA - Purnamasari, Devi; Anggella, Shelly; Saputra, M. Syawal; Hulmansyah, Danil (Awal Bros Journal of Community Development, 2024)
Drug abuse among adolescents is one of the serious problems faced by modern society today. Adolescents as the next generation of the nation are very vulnerable to the negative effects of drugs that can damage their future. This article aims to identify the factors that cause drug abuse among adolescents, the negative impacts it causes, and effective strategies for prevention and control. Through a participatory approach in community service activities, we involve various parties including parents, educators, and local communities to raise awareness of the dangers of drugs. The results of this activity show that intensive education, strict supervision, and moral and emotional support from family and community are very important in preventing drug abuse among adolescents. In addition, rehabilitation and social reintegration programs for adolescents who have become drug users must also be strengthened.